Inflammation Induced Sensory Nerve Growth and Pain Hypersensitivity Requires the N-Type Calcium Channel Cav2.2 - Pitake, Saumitra; Middleton, Leah J.; Abdus-Saboor, Ishmail; Mishra, Santosh K. (Frontiers in Neuroscience, 2019)
Voltage-gated calcium channels (VGCCs) are important mediators of pain hypersensitivity during inflammatory states, but their role in sensory nerve growth remains underexplored. Here, we assess the role of the N-type calcium channel Cav2.2 in the complete Freund’s adjuvant (CFA) model of inflammatory pain. We demonstrate with in situ hybridization and immunoblotting, an increase in Cav2.2 expression after hind paw CFA injection in sensory neurons that respond to thermal stimuli, but not in two different mechanosensitive neuronal populations. Further, Cav2.2 upregulation post-CFA correlates with thermal but not mechanical hyperalgesia in behaving mice, and this hypersensitivity is blocked with a specific Cav2.2 inhibitor. Voltage clamp recordings reveal a significant increase in Cav2.2 currents post-CFA, while current clamp analyses demonstrate a significant increase in action potential frequency. Moreover, CFA-induced sensory nerve growth, which involves the extracellular signal-related kinase (ERK1/2) signaling pathway and likely contributes to inflammation-induced hyperalgesia, was blocked with the Cav2.2 inhibitor. Together, this work uncovers a role for Cav2.2 during inflammation, demonstrating that VGCC activity can promote thermal hyperalgesia through both changes in firing rates of sensory neurons as well as promotion of new neurite outgrowth.